Leaf litter decomposition in remote oceanic island streams is driven by microbes and depends on litter quality and environmental conditions - Ferreira, Verónica (2016)
1. Leaf litter decomposition is an important process in many streams. The flow of carbon and nutrients to higher trophic levels generally depends on litter characteristics and environmental conditions, and is driven by the activities of microbes and invertebrate shredders. However, little is known about what drives litter decomposition in oceanic islands, where invertebrate communities are species-poor. 2. In this study, we assessed the relative importance of litter quality and environmental conditions on the biological colonisation and decomposition of litter exposed to and protected from macroinvertebrates, in the Azores archipelago, North Atlantic Ocean. Three leaf litter species with distinct physical and chemical characteristics (Acacia melanoxylon, Clethra arborea and Pittosporum undulatum) were incubated in six streams with distinct water characteristics. Coarse and fine mesh bags were used to isolate the relative role of macroinvertebrates on litter decomposition. Incubation of litter took place in late spring – early summer and lasted for up to 56 days. 3. No significant differences in litter decomposition rates were found between coarse and fine mesh bags suggesting that microbes, especially aquatic hyphomycetes, are the key players in litter decomposition in these island streams. 4. Litter decomposition rates were inversely proportional to initial lignin concentration: A. melanoxylon 0.0080 day 1 , C. arborea 0.0121 day 1 , P. undulatum 0.0292 day 1 , on average across streams. 5. Litter decomposition rates and associated decomposers differed among streams, suggesting that environmental conditions (e.g. nutrient concentration) may be important moderators of biological activities in these streams, as found for continental streams. 6. Species richness, fungal biomass and reproductive activity of aquatic hyphomycetes on decomposing litter were recorded in Atlantic islands for the first time and were at levels similar to those found for continental streams. 7. High microbial activities in Atlantic island streams ensure litter decomposition when shredder abundance is low.